Habilidades blandas y su influencia en el desempeño laboral en el área de emergencia del hospital Dr. Napoleón Dávila Córdova de Chone - Andrade Bravo, Lady Victoria (2024)
The topic of this research was conducted at the Dr. Napoleón Dávila Córdova Hospital in Chone canton, which had a significant objective of analyzing soft skills and their influence on the job performance of public servants in the emergency area. To achieve this, it was suggested to use inductive, deductive, analytical, and synthetic methods, as well as the application of research techniques such as interviews and surveys, which were very helpful for obtaining results directly from those involved in the research, with the sole aim of gathering more relevant and reliable information. Thus, the correct formulation of each research objective and its activities began, observing certain shortcomings that were affecting the proper functioning of the institution, such as a lack of empathy with patients, who were not provided with pertinent and adequate information about care protocols. Additionally, the staff is not continuously trained to improve their skills and abilities as they should, leading to demotivation and high levels of job stress, which can result in unintentional errors in their functions. Finally, a plan for improvement was proposed through the 5W+1H matrix, involving the authorities of the general hospital in Chone canton with strategies for strengthening soft skills and their influence on the job performance of public servants in the emergency area.